Methods of fabricating a segregation layer over a substrate and methods of fabricating a device
Patent Information
- Application Number
- CN202180019871.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-11
- Filing Date
- 2021-03-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-03-08
AI Technical Summary
但是,专利文献2中仅确认了图案化能力,自偏析并未得到确认
[0021]该方法可以通过一个施加工艺制作偏析层。该方法可以减少在基材上分别施加旋涂碳涂层和抗反射涂层的时间和成本。偏析层可以具有富含硅的上表面。偏析层的上表面可以表现出良好的反射率。偏析层可以表现出良好的蚀刻速率和抗蚀刻性,并且可以通过高碳材料进行调整。该方法可以形成均匀性好的偏析层。该方法制成的偏析层可以减少空隙和/或缺陷。偏析层可以表现出良好的热稳定性。该方法中使用的组合物可以表现出良好的间隙填充特性。偏析层可以表现出良好的耐溶剂性并且可以避免与上层光致抗蚀剂组合物/层混合。偏析层的上表面可以表现出光致抗蚀剂组合物/层的良好润湿性。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] This invention relates to a method for fabricating a segregation layer over a substrate. Furthermore, this invention relates to methods for fabricating photoresist layers, photoresist patterns, processed substrates, and devices. Background Technology
[0002] The demand for smaller, higher-performance devices necessitates finer patterning in devices such as semiconductors and FPDs. Photolithography, using photoresists (hereinafter referred to as "resist / photoresist"), is commonly used for this fine-grained fabrication. To support highly precise resist patterning, other functional layers have been developed, such as top anti-reflective coatings (TARC), bottom anti-reflective coatings (BARC), and spin-on carbon (SOC) coatings. However, such multilayer structures can complicate manufacturing processes and potentially increase time and cost.
[0003] In this context, a specific process concept using a three-layer photoresist was proposed to limit crystallization defects introduced into the semiconductor device during ion implantation (Patent Document 1). However, some of these concepts were not demonstrated by any experiments in Patent Document 1.
[0004] To reduce the number of processing steps in semiconductor manufacturing, a method of segregating a self-segregating polymer composition onto a photoresist layer on a BARC layer has been proposed (Patent Document 2). However, only the patterning capability is confirmed in Patent Document 2; self-segregation is not confirmed.
[0005] Reference List
[0006] [Patent Literature]
[0007] [Patent Document 1] US2014 / 0061738A
[0008] [Patent Document 2] US2010 / 0009132A
[0009] [Patent Document 3] US9274426B2 Summary of the Invention
[0010] [Technical Issues]
[0011] The inventors have identified one or more significant problems that still require improvement, as listed below: difficulty in obtaining a segregated layer with good performance by a single application (coating) process; time-consuming and costly individual application processes for multiple layers; difficulty in obtaining a silicon-rich upper surface in the segregated layer; insufficient reflectivity of the upper surface of the segregated layer; insufficient etch rate of the segregated layer, and / or difficulty in adjusting for good process adaptability; insufficient uniformity of the segregated layer; a large number of voids and / or defects in the segregated layer; insufficient thermal stability of the segregated layer; insufficient composition used in the method to fill gaps; insufficient solvent resistance of the upper surface of the segregated layer, making it difficult to avoid mixing with the upper photoresist composition / layer; difficulty in applying a photoresist composition / layer over a segregated layer with good wettability.
[0012] The inventors then discovered that the invention described below solves at least one of these problems.
[0013] [Solution to the problem]
[0014] The present invention provides a method for manufacturing segregated layers over a substrate, comprising: (1) applying a composition over the substrate, wherein the composition comprises a solvent (A), a siloxane polymer (B), and a high-carbon material (C); and (2) heating the substrate to form segregated layers consisting of an antireflective coating made of the siloxane polymer (B) and a spin-coated carbon coating made of the high-carbon material (C), wherein the antireflective coating, the spin-coated carbon coating, and the substrate are disposed sequentially.
[0015] The present invention also provides a method for manufacturing a photoresist layer, comprising: (3) applying a photoresist composition over a segregation layer; and (4) heating the substrate to form a photoresist layer.
[0016] The present invention also provides a method for manufacturing a photoresist pattern, comprising: (5) exposing a photoresist layer; and (6) developing the exposed layer to form a photoresist pattern.
[0017] The present invention also provides a method for manufacturing a processed substrate, comprising: (7) etching with a resist pattern as a mask; and (8) processing the substrate.
[0018] Furthermore, the present invention provides a method for manufacturing a device.
[0019] Another aspect of the present invention provides a composition for self-segregation into an anti-reflective coating and a spin-coated carbon coating, comprising a solvent (A), a siloxane polymer (B), and a high-carbon material (C).
[0020] [Effects of the Invention]
[0021] This method can fabricate a segregated layer through a single application process. It reduces the time and cost of separately applying spin-coated carbon and anti-reflective coatings to a substrate. The segregated layer can have a silicon-rich upper surface. The upper surface of the segregated layer can exhibit good reflectivity. The segregated layer can exhibit good etch rate and etch resistance, and can be tuned using high-carbon materials. This method can form a segregated layer with good uniformity. The segregated layer produced by this method can reduce porosity and / or defects. The segregated layer can exhibit good thermal stability. The composition used in this method can exhibit good gap-filling properties. The segregated layer can exhibit good solvent resistance and can avoid mixing with the upper photoresist composition / layer. The upper surface of the segregated layer can exhibit good wettability of the photoresist composition / layer. Attached Figure Description
[0022] Figure 1 This is silicon content assessment data. Figure 1 In this context, "invention c." means "inventive composition".
[0023] [Explanation of the Implementation Plan]
[0024] The above overview and the following detailed description are provided to illustrate the invention and are not intended to limit the scope of the claimed invention. Detailed Implementation
[0025] Throughout this specification, unless expressly limited or stated otherwise, the following definitions, symbols, units, abbreviations, and terms have the meanings given in the following definitions, descriptions, and examples.
[0026] The use of the singular includes the plural, and "a," "an," and "the" mean "at least one." Furthermore, the word "contains," along with other forms such as "comprises" and "containing," are not restrictive. Similarly, terms such as "element" or "component" cover both elements or components that comprise one unit and an element or component, and elements or components that comprise more than one unit.
[0027] The term “and / or” refers to any combination of the above elements, including the use of a single element.
[0028] When a numerical range is described using "to", "-", or "~", the range includes the numbers before and after the "to", "-", or "~", and the units of the two numbers are the same. For example, "5 to 25 mol%" means "5 mol% or more and 25 mol% or less".
[0029] The "C" used in this article x-y “C” x -C y "and "C xTerms like "" indicate the number of carbon atoms in a molecule or substituent. For example, "C 1-6 "Alkyl" refers to an alkyl chain having 1 to 6 carbon atoms (e.g., methyl, ethyl, propyl, butyl, pentyl, hexyl, etc.).
[0030] When the polymers described herein have multiple types of repeating units, these repeating units are copolymerized. The copolymer can be any form selected from alternating copolymerization, random copolymerization, block copolymerization, graft copolymerization, and any combination thereof. When the polymer or resin is represented by a chemical structure, the n, m, etc. outside the parentheses indicate the number of repetitions.
[0031] The temperature unit used in this article is Celsius. For example, "20 degrees" means "20 degrees Celsius".
[0032] When describing additives (e.g., crosslinking agents, surfactants), an additive means that the compound itself performs its function. For example, describing a base-generating agent means that the compound generates a base. As a practical embodiment, such a compound can be dissolved or dispersed in a solvent and then included in the composition. As an embodiment of the invention, such a solvent is preferably included in the segregation composition as solvent (A).
[0033] Composition
[0034] The following describes a composition applied to a substrate in the manufacturing method of the present invention. Since this composition segregates into an anti-reflective coating and a spin-coated carbon coating, it can be described as a segregating composition. In one embodiment of the invention, the composition consists essentially of a segregating composition.
[0035] The composition comprises a solvent (A), a siloxane polymer (B), and a high-carbon material (C).
[0036] In another embodiment of the invention, the composition self-segregates into an anti-reflective coating and a spin-coated carbon coating, and comprises the anti-reflective coating and the spin-coated carbon coating.
[0037] Another aspect of the invention is the use of the composition to self-segregate into an anti-reflective coating and a spin-coated carbon coating, wherein the composition comprises an anti-reflective coating and a spin-coated carbon coating.
[0038] Solvent (A)
[0039] Solvent (A) may comprise any type of solvent. In one embodiment of the invention, solvent (A) comprises an organic solvent. Preferably, the organic solvent comprises a hydrocarbon solvent, an ether solvent, an ester solvent, an alcohol solvent, a ketone solvent, or any mixture thereof.
[0040] (A) Examples of solvents include: aliphatic hydrocarbon solvents, such as n-pentane, isopentane, n-hexane, isohexane, n-heptane, isoheptane, cyclohexane, and methylcyclohexane; aromatic hydrocarbon solvents, such as benzene, toluene, xylene, ethylbenzene, trimethylbenzene, methyl ethylbenzene, n-propylbenzene, isopropylbenzene, diethylbenzene, and isobutylbenzene; and monohydric alcohol solvents, such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-pentanol, isopentanol, 2-methylbutanol, 2-ethylhexanol, n-nonanol, 2,6-dimethylheptanol-4, n-decanol, cyclohexanol, benzyl alcohol, benzyl methanol, diacetone alcohol, and... Cresol; polyol solvents, such as ethylene glycol, propylene glycol, 1,3-butanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, and glycerol; ketone solvents, such as acetone, methyl ethyl ketone, methyl n-propyl ketone, methyl n-butyl ketone, diethyl ketone, trimethyl nonanone, cyclohexanone, cyclopentanone, methyl cyclohexanone, 2,4-pentanedione, acetone-based acetone, acetophenone, and fentanyl ketone; ether solvents, such as diethyl ether, isopropyl ether, n-butyl ether (DBE), n-hexyl ether, 2-ethylhexyl ether, dimethyl dioxane, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol diethyl ether, ethylene glycol mono-n-butyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol monomethyl ... Hexyl ether, ethylene glycol monophenyl ether, ethylene glycol mono-2-ethylbutyl ether, ethylene glycol dibutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol diethyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol di-n-butyl ether, diethylene glycol mono-n-hexyl ether, propylene glycol monomethyl ether (PGME), propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tetrahydrofuran and 2-methyltetrahydrofuran; ester solvents, such as diethyl carbonate, methyl acetate, ethyl acetate, γ-butyrolactone, γ-valerolactone, n-Propyl acetate, isopropyl acetate, n-butyl acetate (nBA), isobutyl acetate, n-decyl acetate, n-butyl propionate, methyl lactate, ethyl lactate (EL), γ-butyrolactone, n-butyl lactate, n-pentyl lactate, diethyl malonate, dimethyl phthalate, diethyl phthalate, propylene glycol 1-monomethyl ether 2-acetate (PGMEA), di(propylene glycol) methyl ether acetate (Di(PGMEA)), propylene glycol monoethyl ether acetate, cyclohexyl hexanoate, and propylene glycol monopropyl ether acetate; nitrogen-containing solvents, such as N-methylformamide; and sulfur-containing solvents, such as dimethyl sulfide. Any mixture of any of these solvents may also be used.
[0041] In one embodiment of the invention, solvent (A) comprises at least one high-boiling-point solvent, preferably Di(PGMEA), cyclohexyl hexanoate, n-decyl acetate, and any mixture thereof; more preferably Di(PGMEA), n-decyl acetate, and any mixture thereof; and even more preferably a mixture of Di(PGMEA) and n-decyl acetate. While not wishing to be bound by theory, the inventors believe that the presence of a high-boiling-point solvent allows for an extended drying time of the composition after application to the substrate, thereby enabling better segregation of components to separate the layers. Solvents other than high-boiling-point solvents in solvent (A) may be alkaline solvents.
[0042] In one embodiment of this type of invention, the boiling point of the high-boiling solvent is 50% or more higher than that of the alkaline solvent (preferably 50-150%, more preferably 70-125%). If multiple high-boiling solvents or alkaline solvents are present in solvent (A), the boiling point is obtained by averaging their respective values.
[0043] The alkaline solvent is preferably PGME, PGMEA, EL, nBA, DBE, and any mixture thereof; more preferably PGME, PGMEA, and mixtures thereof; and even more preferably a mixture of PGME and PGMEA.
[0044] The mass ratio of high-boiling-point solvent to alkaline solvent is preferably 5-30%; more preferably 10-25%, and even more preferably 10-20%.
[0045] If the high-boiling-point solvent or the alkaline solvent is a mixture of two or more substances, the mass ratio of the first solvent to the second solvent is preferably 90:10 to 10:90; more preferably 80:20 to 20:80. If the high-boiling-point solvent or the alkaline solvent is a mixture of three or more substances, the mass ratio of the first solvent to the total of the three substances is preferably 30 to 90% (more preferably 50 to 80%, even more preferably 60 to 70%); the ratio of the second solvent to the total of the three substances is preferably 10 to 50% (more preferably 20 to 40%); and the ratio of the third solvent to the total of the three substances is preferably 5 to 40% (more preferably 5 to 20%, even more preferably 5 to 15%).
[0046] Solvent (A) preferably contains an organic solvent, and the water content in solvent (A) is preferably less than 0.1% by mass, more preferably less than 0.01% by mass. Considering its relationship with another layer or coating, it is preferable that solvent (A) is water-free.
[0047] In one embodiment of the invention, the mass ratio of solvent (A) is 60-99% by mass based on the total mass of the segregating composition; preferably 70-97% by mass; more preferably 80-95% by mass; and even more preferably 90-95% by mass.
[0048] Siloxane polymers (B)
[0049] The siloxane polymer (B) may contain at least one unit selected from the group consisting of unit B1, unit B2 and unit B3.
[0050] Unit B1 is represented by equation B1.
[0051]
[0052] Ah 11 It is C 1-5 Aliphatic hydrocarbons. Ah 11 Preferably, it is methyl, ethyl, n-propyl, isopropyl, tert-butyl, vinyl (H2C=CH-) or ethynyl (HC≡C-); more preferably methyl or tert-butyl; and even more preferably methyl.
[0053] R 12 Yes - Ah 12 -O-Ah 12 -O-*, -Si(H) p12 (Ah 12 ) q12 -O-Si(H) p12 (Ah 12 ) q12 Or a single key that connects to other units. R 12 Preferred is -Ah 12 -O-Ah 12 -Si(H) p12 (Ah 12 ) q12 Or -O-Si(H) p12 (Ah 12 ) q12 More preferably -Ah 12 , or -O-Si(H) p12 (Ah 12 ) q12 Further optimization - Ah 12 In one embodiment of the invention, R 12 It is -O-Si(H) p12 (Ah 12 ) q12 .
[0054] The asterisk (*) indicates a single bond that connects to other units and / or the polymer terminus. This single bond can be bonded to other units via another single bond in the polymer and / or an aliphatic hydrocarbon. The term "other units" does not include a unit B1 containing this single bond. However, in the case where the siloxane polymer (B) contains multiple units B1, this single bond can be bonded to other units B1 (units B1 that do not contain this single bond and do not self-crosslink with unit B1). Unless otherwise specified, the same applies below.
[0055] "A single bond that connects to other units" refers to a single bond that is bonded to other units. Unless otherwise specified, the same applies below.
[0056] Ah 12 It is C 1-5 Aliphatic hydrocarbons. Ah 12 Preferably, it is methyl, ethyl, n-propyl, isopropyl, tert-butyl, vinyl, or ethynyl; more preferably methyl, tert-butyl, or vinyl; even more preferably methyl or vinyl, and even more preferably methyl.
[0057] The following is an exemplary siloxane polymer (B) comprising two units B1. The two middle units B1 provide -O-* R 12 And a single bond that combines with other units. The middle two units B1 have Ah... 11 Each of them is a methyl group.
[0058]
[0059] p12 = 0, 1, 2, or 3. p12 is preferably 0 or 1; more preferably 0. q12 = 0, 1, 2, or 3. q12 is preferably 2 or 3; more preferably 3. p12 + q12 = 3.
[0060] L 11 It is a single bond or -O-; -O- is preferred.
[0061] n 11 It is the number of repetitions of unit B.
[0062] The following example illustrates unit B1, but is not intended to limit the scope of the claims of this invention.
[0063]
[0064] Unit B2 is represented by equation B2.
[0065]
[0066] R 21 Yes - Ah 21 -O-Ah 21 -O-*, -Si(H) p21 (Ah21 ) q21 -O-Si(H) p21 (Ah 21 ) q21 Or a single key that connects to other units. R 21 Preferred is -O-Ah 21 -O-*, -Si(H) p21 (Ah 21 ) q21 -O-Si(H) p21 (Ah 21 ) q21 Or a single bond that connects to other units; more preferably -O-Ah 21 -Si(H) p21 (Ah 21 ) q21 or -O-Si(H) p21 (Ah 21 ) q21 Further optimization of -O-Si(H) p21 (Ah 21 ) q21 .
[0067] R 22 Yes - Ah 22 -O-Ah 22 -O-*, -Si(H) p22 (Ah 22 ) q22 -O-Si(H) p22 (Ah 22 ) q22 Or a single key that connects to other units. R 22 Preferred is -O-Ah 22 -O-*, -Si(H) p22 (Ah 22 ) q22 -O-Si(H) p22 (Ah 22 ) q22 Or a single bond that connects to other units; more preferably -O-Ah 22 -Si(H) p22 (Ah 22 ) q22 Or -O-Si(H) p22 (Ah 22 ) q22 Further optimization of -O-Si(H) p22 (Ah 22 ) q22 .
[0068] Ah 21 and Ah22 Each is C independently 1-5 Aliphatic hydrocarbons. Ah 21 and Ah 22 Each of the following is preferably methyl, ethyl, n-propyl, isopropyl, tert-butyl, vinyl (H2C=CH-) or ethynyl (HC≡C-); more preferably methyl or tert-butyl; and even more preferably methyl.
[0069] p21, p22, q21, and q22 are each independently 0, 1, 2, or 3. p21 and p22 are each preferably 0 or 1; more preferably 0. q21 and q22 are each preferably 2 or 3; more preferably 3.
[0070] p21+q21=p22+q22=3.
[0071] L 21 It is a single bond or -O-; -O- is preferred.
[0072] n 21 It is the number of repetitions of unit B2.
[0073] The following example illustrates unit B2, but is not intended to limit the scope of the claims of this invention.
[0074]
[0075] Unit B3 is represented by equation B3.
[0076]
[0077] R 31 Yes - Ah 31 -O-Ah 31 -O-*, -Si(H) p31 (Ah 31 ) q31 -O-Si(H) p31 (Ah 31 ) q31 Or a single key that connects to other units. R 31 Preferred is -Ah 31 -O-Ah 31 -Si(H) p31 (Ah 31 ) q31 -O-Si(H) p31 (Ah 31 ) q31 More preferably -Ah 31 , or -O-Si(H) p31 (Ah 31 ) q31 Further optimization - Ah 31In one embodiment of the invention, R 31 It is -O-Si(H) p31 (Ah 31 ) q31 .
[0078] Ah 31 It is C 1-5 Aliphatic hydrocarbons. Ah 31 Preferably, it is methyl, ethyl, n-propyl, isopropyl, tert-butyl, vinyl, or ethynyl; more preferably methyl, tert-butyl, or vinyl; even more preferably methyl or vinyl, and even more preferably methyl.
[0079] p31 = 0, 1, 2, or 3. p31 is preferably 0 or 1; more preferably 0. q31 = 0, 1, 2, or 3. q31 is preferably 2 or 3; more preferably 3. p31 + q31 = 3.
[0080] R 32 It is a group consisting of at least two groups and / or linkers selected from the group consisting of: phenyl, phenylene, -O-, -(C=O)-, -COO-, -COOH, -NH-, C 1-5 Aliphatic hydrocarbon groups and C 1-5 Aliphatic hydrocarbon linker. R 32 One linker can bond with another linker to form a hydrocarbon ring or heterocyclic group; preferably an aromatic ring or heteroaryl; more preferably a heteroaryl.
[0081] The following is an exemplary siloxane polymer (B) containing unit B3. 32 It is composed of a combination of n-propylene (C3 aliphatic hydrocarbon linker), -NH-, -(C=O)-, sec-butylene (C4 aliphatic hydrocarbon linker) and -(C=O)- in sequence, wherein the terminal -(C=O)- is bonded to -NH- to form a heteroaryl group.
[0082]
[0083] In one embodiment of the present invention, R 32 It is a group consisting of preferably 2 to 7 (more preferably 2 to 6; even more preferably 3 to 5) groups and / or linking groups.
[0084] In one embodiment of the present invention, R 32 It is a group consisting of at least two groups and / or linkers selected from the group consisting of: phenyl, phenylene, -O-, -(C=O)-, -COO-, -COOH, -NH-, C 1-5 Aliphatic hydrocarbon groups and C 1-5 Aliphatic hydrocarbon linking groups; more preferably phenylene, -O-, -(C=O)-, -COO-, -NH-, C1-5 Aliphatic hydrocarbon groups and C 1-5 Aliphatic hydrocarbon linker.
[0085] L 31 It is a single bond or -O-; -O- is preferred.
[0086] n 31 It is the number of repetitions of unit B3.
[0087] The following example illustrates unit B3, but is not intended to limit the scope of the claims of this invention.
[0088]
[0089]
[0090] Although they did not want to be bound by theory, the inventors believed that protecting groups (such as tert-butyl, methoxymethyl ether) were used to maintain the hydrophobicity of the polysiloxane layer until phase separation occurred.
[0091] The weight-average molecular weight (Mw) of the siloxane polymer (B) is preferably 1,000 to 100,000; more preferably 2,000 to 50,000; even more preferably 3,000 to 20,000; and even more preferably 3,000 to 10,000.
[0092] Mw and Mn (number-average molecular weight) can be measured by known methods. When the sample is a polymer, in a preferred embodiment, the measurement method is the method used in the embodiments of the invention, as described below. Monodisperse polystyrene can be used as a standard.
[0093] n 11 n 21 and n 31 This represents the number of repetitions of units B1, B2, and B3 in the siloxane polymer (B). 0% ≤ n 11 / (n 11 +n 21 +n 31 )≤80%, 0%≤n 21 / (n 11 +n 21 +n 31 )≤80%, 0%≤n 31 / (n 11 +n 21 +n 31 ≤80%.
[0094] n 11 / (n 11 +n 21 +n 31Preferably 5-75%; more preferably 10-70%; even more preferably 20-70%; even more preferably 30-70%.
[0095] n 21 / (n 11 +n 21 +n 31 Preferably 0-75%; more preferably 0-70%; even more preferably 0-60%; even more preferably 0-40%.
[0096] n 31 / (n 11 +n 21 +n 31 Preferably 5-75%; more preferably 10-60%; even more preferably 10-50%; even more preferably 10-40%.
[0097] As exemplary embodiments of the siloxane polymer (B), those used in the embodiments described later can be listed.
[0098] In one embodiment of the invention, the siloxane polymer (B) is 0.1 to 10% by mass based on the total mass of the segregated composition; preferably 0.2 to 5% by mass; more preferably 0.5 to 5% by mass; further preferably 0.75 to 3% by mass; and even more preferably 0.90 to 2% by mass.
[0099] High-carbon materials (C)
[0100] The spin-coated carbon coating produced by this invention is made of a high-carbon material (C). Here, "made of" means that the coating structure is mainly composed of the high-carbon material (C) itself or compounds / polymers formed therefrom. For example, in one embodiment of the invention, a crosslinking agent (E) can be part of the spin-coated carbon coating.
[0101] The spin-coated carbon coating of the present invention preferably exhibits high etch resistance. In a preferred embodiment of the present invention, the number of atoms contained in the spin-coated carbon coating satisfies the following formula C1.
[0102] 1.5 ≤ {total number of atoms / (number of C atoms - number of O atoms)} ≤ 3.5 (Equation C1)
[0103] The number of C atoms represents the number of carbon atoms in the total number of atoms, while the number of O atoms represents the number of oxygen atoms in the total number of atoms. The total number of atoms in formula C1 includes the number of hydrogen atoms.
[0104] It can be said that the atoms are in the solid component of the portion of the composition coated with spin-coated carbon. Alternatively, the solid component of the spin-coated carbon coating can be said to be the component that forms the spin-coated carbon coating. For example, atoms in the solvent (A) are ignored when calculating the aforementioned atoms.
[0105] Formula C1 is preferably Formula C1'; Formula C1 is more preferred.
[0106] 1.5 ≤ {total number of atoms / (number of C atoms - number of O atoms)} ≤ 2.4 (Equation C1')
[0107] 1.8 ≤ {total number of atoms / (number of C atoms - number of O atoms)} ≤ 2.4 (Equation C1”)
[0108] The high-carbon material (C) may include at least one selected from the group consisting of unit C2, molecule C3 and unit C4.
[0109] Unit C2 is represented by formula C2. Unit C2 can constitute a polymer.
[0110]
[0111] Ar 41 Is it unsubstituted or substituted with R? 41 C 6-60 Hydrocarbons. Ar is preferred. 41 It does not contain fused aromatic rings. Ar 41 Preferably, it contains 9,9-diphenylfluorene, 9-phenyl-fluorene, phenyl, or C. 6-60 Linear polyphenyl and C 6-60 Branched polyphenyl groups, each of which can be substituted with R 41 .
[0112] R 41 Is it a linear, branched, or cyclic C? 1-20 Alkyl, amino, or alkylamino; preferably straight-chain, branched, or cyclic C 1-10 Alkyl, or alkylamino; more preferably straight-chain C 1-3 Alkyl, branched C 1-3 Alkyl, cyclopentyl, cyclohexyl or dimethylamino.
[0113] When a high-carbon material (C) contains multiple C2 units, R 41 It can be between multiple Ar 41 They are then combined into a connecting base. An Ar 41 It can replace one or more R 41 Preferred replacement has one R 41 .
[0114] In a unit C2, the group enclosed in parentheses (e.g., the group enclosed in parentheses, with p described next to the parentheses) 41 ) can be used with R 41 Bonding. In this case, the group and Ar 41 Through R as the connection base 41 Combine them.
[0115] R12 It is I, Br or CN; preferably I or Br; more preferably I.
[0116] p 41 It is a number from 0 to 5. As one embodiment of the invention, the high-carbon material (C) can be composed of two C2 units one after another. An example of this embodiment is two Ar units. 41 Both are phenyl groups, one p 41 It's 1, the other p 41 It is 2. In this case, p 41 The overall value is 1.5. Unless otherwise specified, the same applies throughout this manual.
[0117] p 41 Preferably 0, 1, 2, or 3; more preferably 0, 1, or 2; further preferably 0 or 1; even more preferably 0. In another preferred embodiment of the invention, p 41 The value is 1.
[0118] p 42 It is a number from 0 to 1; preferably 0 or 1; more preferably 1.
[0119] q 41 It refers to the numbers 0 to 5. q 41 Preferably 0, 1, 2, or 3; more preferably 0, 1, or 2; further preferably 0 or 1; even more preferably 0. In another preferred embodiment of the invention, q 41 The value is 1.
[0120] q 42 It is a number from 0 to 1; preferably 0 or 1; more preferably 1.
[0121] r 41 It is a number from 0 to 5; preferably 0, 1, 2, 3, 4, or 5; more preferably 0, 1, 2, or 3; further preferably 1 or 2; even more preferably 1. In another preferred embodiment of the invention, r 41 It is 0.
[0122] s 41 It refers to the numbers 0 to 5. 41 Preferably 0, 1, 2, or 3; more preferably 0, 1, or 2; further preferably 0 or 1; even more preferably 0. In another preferred embodiment of the invention, r 41 The value is 1.
[0123] In a preferred embodiment of the present invention, p 41 q 41 and r 41 In a unit C2, the values are not all 0 at the same time.
[0124] When the high-carbon material (C) is a polymer, its molecular weight is expressed as weight-average molecular weight (Mw).
[0125] Preferably, the high-carbon material (C) containing unit C2 has a molecular weight of 500 to 4,000; more preferably 500 to 3,000; and even more preferably 1,000 to 2,000.
[0126] Exemplary unit C2 is described below, but is not intended to limit the scope of the invention.
[0127]
[0128]
[0129] The molecule C3 is represented by the formula C3. The molecule C3 can serve as a unit to form polymers of high-carbon materials (C).
[0130]
[0131] Ar 51 It is a single key, C 1-6 Alkyl, C 6-12 cycloalkyl or C 6-14 Aryl. 51 Preferred single bond, C 1-6 Alkyl or phenyl; more preferably single bond, straight-chain C3 alkyl, straight-chain C6 alkyl, tert-butyl or phenyl; even more preferably single bond or phenyl; even more preferably phenyl.
[0132] Ar 52 It is C 1-6 Alkyl, C 6-12 cycloalkyl or C 6-14 Aryl. 52 Preferably, it is isopropyl, tert-butyl, C6 cycloalkyl, phenyl, naphthyl, phenanthrene, or biphenyl; more preferably, it is phenyl.
[0133] R 51 and R 52 Each independently is C 1-6 Alkyl, hydroxyl, halogen, or cyano groups. R 51 and R 52 Each of the following is preferably methyl, ethyl, propyl, isopropyl, tert-butyl, hydroxyl, fluorine, chlorine or cyano; more preferably methyl, hydroxyl, fluorine or chlorine.
[0134] R 53 It is hydrogen, C 1-6 Alkyl or C 6-14 Aryl. R 53 Preferably hydrogen or C 1-6 Alkyl or phenyl; more preferably hydrogen, methyl, ethyl, straight-chain C5 alkyl, tert-butyl or phenyl; even more preferably hydrogen or phenyl; even more preferably hydrogen.
[0135] In Ar 52 C 1-6 Alkyl or C 6-14 Aryl and R 53 C 1-6 Alkyl or C 6-14 In the case of aryl, Ar 52 and R 53 They can bond with each other to form hydrocarbon rings.
[0136] r 51 and r 52 Each is an integer from 0 to 5. 51 and r 52 Each is preferably 0 or 1; more preferably 0.
[0137] Cy surrounded by dashed lines 51 Cy 52 and Cy 53 The rings can optionally and independently be adjacent aromatic rings Ph 51 Fused aromatic rings.
[0138] Cy surrounded by dashed lines 54 Cy 55 and Cy 56 The rings can optionally and independently be adjacent aromatic rings Ph 52 Fused aromatic rings.
[0139] R 51 R 52 The bonding positions with OH are not restricted.
[0140] The following compound is an exemplary embodiment of the present invention, molecule C3. Aromatic ring Ph 51 and aromatic ring Cy 53 They fuse together to form a naphthalene ring, and the OH group reacts with the aromatic ring Cy. 53 Bonding. Furthermore, Ar 51 For a single bond, Ar 52 and R 53 It is phenyl, while Ar 52 and R 53 They bond together to form a hydrocarbon ring (fluorene).
[0141]
[0142] An exemplary molecule C3 is described below, but it is not intended to limit the scope of the invention.
[0143]
[0144] Unit C4 is represented by equation C4.
[0145]
[0146] R 61 It is hydrogen, C 1-6 Alkyl, halogen, or cyano; preferably hydrogen, methyl, or tert-butyl; more preferably hydrogen or methyl; even more preferably hydrogen.
[0147] R 62 It is C 1-6 Alkyl, halogen, or cyano; preferably methyl or tert-butyl; more preferably methyl.
[0148] p 61 It represents the number of repetitions. 62 It is an integer from 0 to 5; preferably 0 to 1; more preferably 0.
[0149] As one embodiment of the invention, the high-carbon material (C) may comprise units C2, molecules C3, and units C4 of various substances. Such exemplary embodiments are described below, but are not intended to limit the scope of the invention.
[0150]
[0151]
[0152] In one embodiment of the invention, the mass percentage of the high-carbon material (C) based on the total mass of the segregated composition is 0.5 to 30% by mass; preferably 1 to 20% by mass; more preferably 3 to 15% by mass; even more preferably 5 to 10% by mass; and even more preferably 5 to 8% by mass.
[0153] Thermal acid generator (D)
[0154] The composition used in the manufacturing method of the present invention may comprise a thermal acid generator (D) and / or a crosslinking agent (E). Upon heating, the thermal acid generator (TAG) can generate an acid; preferably a strong acid. The generated acid catalyzes the reaction of the crosslinking agent (E), facilitating processing at lower temperatures and shortening reaction time to form an antireflective coating.
[0155] Preferred TAGs are those that are activated at temperatures exceeding 80 degrees Celsius. Examples of TAGs include metal-free sulfonium and metal-free iodonium salts, such as strongly non-nucleophilic triarylsulfonium, dialkylarylsulfonium, and diarylalkylsulfonium salts, as well as strongly non-nucleophilic alkylaryliodonium and diaryliodonium salts; and strongly non-nucleophilic ammonium salts, alkylammonium salts, dialkylammonium salts, trialkylammonium salts, and tetraalkylammonium salts.
[0156] In addition, covalent TAGs are also useful, examples of which include 2-nitrobenzyl esters of alkyl or aryl sulfonic acids and other sulfonates that thermally decompose to produce free sulfonic acids. Examples include diaryliodonium perfluoroalkyl sulfonates, diaryliodonium tri(fluoroalkylsulfonyl)methylates, diaryliodonium bis(fluoroalkylsulfonyl)methylates, diaryliodonium bis(fluoroalkylsulfonyl)imides, and diaryliodonium quaternary ammonium perfluoroalkyl sulfonates. Examples of unstable esters include 2-nitrobenzyl toluenesulfonate, 2,4-dinitrobenzyl toluenesulfonate, 2,6-dinitrobenzyl toluenesulfonate, and 4-nitrobenzyl toluenesulfonate; benzenesulfonates, such as 2-trifluoromethyl-6-nitrobenzyl 4-chlorobenzenesulfonate and 2-trifluoromethyl-6-nitrobenzyl 4-nitrobenzenesulfonate; phenolsulfonates, such as phenyl 4-methoxybenzenesulfonate; tri(fluoroalkylsulfonyl)methyl quaternary ammonium salts; alkyl ammonium salts of organic acids, such as bis(fluoroalkylsulfonyl)imine quaternary alkyl ammonium salts and triethylammonium salts of 10-camphorsulfonic acid. Various aromatic (anthracene, naphthalene, or benzene derivatives) sulfonate ammonium salts can be used as TAGs.
[0157] Exemplary implementations of TAG(D) are described below, but are not intended to limit the scope of the invention.
[0158]
[0159] In one embodiment of the invention, the mass percentage of the hot acid generator (D) based on the total mass of the siloxane polymer (B) is 10-50% by mass; preferably 10-40% by mass; more preferably 15-30% by mass; and even more preferably 20-30% by mass.
[0160] Crosslinking agent (E)
[0161] The crosslinking agent (E) can improve coating formation characteristics and prevent the segregated layer of the present invention from mixing with the upper coating (e.g., a photoresist coating), and eliminate the diffusion of low molecular weight components into the upper coating. By heating, the crosslinking agent (E) can bond with a high carbon material (C) to form a spin-coated carbon coating.
[0162] As crosslinking agents (E), melamine compounds, guanidine compounds, glycourea compounds, or urea compounds may be used, having at least one group selected from hydroxymethyl, alkoxymethyl, and acyloxymethyl groups substituted thereon; epoxy compounds; thioepoxide compounds; isocyanate compounds; azide compounds; and compounds containing double bonds such as alkenyl ether groups. These can be used as additives or introduced as side groups into the polymer side chains. Furthermore, compounds containing hydroxyl groups can also be used as crosslinking agents.
[0163] Examples of the aforementioned epoxy compounds include tris(2,3-epoxypropyl)isocyanurate, trimethylolpropane triglycidyl ether, trimethylolpropane triglycidyl ether, and triethylethane triglycidyl ether. Examples of melamine compounds include hexamethylolmelamine, hexamethoxymethylmelamine, compounds derived from the methoxymethylation of 1 to 6 hydroxymethyl groups of hexamethylolmelamine, and mixtures thereof; hexamethoxyethylmelamine, hexaacyloxymethylmelamine, compounds derived from the acyloxymethylation of 1 to 6 hydroxymethyl groups of hexamethylolmelamine, or mixtures thereof. As guanidine compounds, tetramethylolguanidine, tetramethoxymethylguanidine, compounds derived from the methoxymethylation of 1 to 4 hydroxymethyl groups of tetramethylolguanidine, and mixtures thereof; tetramethoxyethylguanidine, tetraacyloxyguanidine, compounds derived from the acyloxymethylation of 1 to 4 hydroxymethyl groups of tetramethylolguanidine, and mixtures thereof; and tetramethoxyethylguanidine, tetraacyloxyguanidine, compounds derived from the acyloxymethylation of 1 to 4 hydroxymethyl groups of tetramethylguanidine, and mixtures thereof. As urea compounds, tetrahydroxymethyl urea, tetramethoxy urea, tetramethoxymethyl urea, compounds derived from the methoxymethylation of 1 to 4 hydroxymethyl groups of tetrahydroxymethyl urea, or mixtures thereof, compounds obtained by the acyloxymethylation of 1 to 4 hydroxymethyl groups of tetrahydroxymethyl urea, or mixtures thereof, can be used. As urea compounds, tetrahydroxymethyl urea, tetramethoxymethyl urea, compounds derived from the methoxymethylation of 1 to 4 hydroxymethyl groups of tetrahydroxymethyl urea, or mixtures thereof, as well as tetramethoxyethyl urea, can be used.
[0164] As compounds containing an alkenyl ether group, ethylene glycol divinyl ether, triethylene glycol divinyl ether, 1,2-propanediol divinyl ether, 1,4-butanediol divinyl ether, butanediol divinyl ether, neopentyl glycol divinyl ether, trimethylolpropane trivinyl ether, hexanediol divinyl ether, 1,4-cyclohexanediol divinyl ether, pentaerythritol trivinyl ether, pentaerythritol tetravinyl ether, sorbitol tetravinyl ether, sorbitol pentavinyl ether, trimethylolpropane trivinyl ether, etc., can be used.
[0165] Exemplary embodiments of the crosslinking agent (E) are described below, but are not intended to limit the scope of the invention.
[0166]
[0167] In one embodiment of the invention, the mass ratio of the crosslinking agent (E) is 3 to 50% by mass based on the total mass of the high-carbon material (C); preferably 5 to 30% by mass; more preferably 5 to 20% by mass; and even more preferably 8 to 15% by mass.
[0168] Additives (F)
[0169] The composition used in the manufacturing method of the present invention may contain additives (F) other than TAG (D) or crosslinking agent (E). Such additives may include surfactants, thermal alkali generators (TBG), acids, bases, photopolymerization initiators, agents for enhancing adhesion to substrates, or any mixture of these.
[0170] In one embodiment of the invention, the mass ratio of the additive (F) (or the sum of multiple additives if any) is 0 to 10% by mass based on the total mass of the segregating composition; preferably 0.0001 to 5% by mass; more preferably 0.0001 to 3% by mass. In another aspect of the invention, the additive (F) is not included in the segregating composition.
[0171] surfactants
[0172] Surfactants are one embodiment of additives (F). Surfactants can reduce pinholes or streaks in coatings made from the composition and can increase the coatability and / or solubility of the composition.
[0173] The amount of surfactant used is preferably 0-5% by mass; more preferably 0.00001-3% by mass; even more preferably 0.0001-2% by mass; and even more preferably 0.001-2% by mass. In another preferred embodiment of the invention, the composition does not contain any surfactant (0% by mass).
[0174] Examples of surfactants include: polyoxyethylene alkyl ether compounds, such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkyl aryl ether compounds, such as polyoxyethylene octylphenol ether and polyoxyethylene nonylphenol ether; polyoxyethylene-polyoxypropylene block copolymer compounds; sorbitol fatty acid ester compounds, such as sorbitol monolaurate, sorbitol monopalmitate, sorbitol monostearate, sorbitol trioleate, and sorbitol tristearate; and polyoxyethylene sorbitol fatty acid ester compounds, such as polyoxyethylene sorbitol monolaurate, polyoxyethylene sorbitol monopalmitate, polyoxyethylene sorbitol monostearate, and polyoxyethylene sorbitol tristearate. Other examples of surfactants include: fluorosurfactants such as EFTOP (trade names) EF301, EF303 and EF352 (Tohkem Products Corporation), MEGAFACE (trade names) F171, F173, R-08, R-30, R-41 and R-2011 (DICC Corporation), Fluorad FC430 and FC431 (Sumitomo 3M), AsahiGuard (trade name) AG710 (Asahi Glass), and SURFLON S-382, SC101, SC102, SC103, SC104, SC105 and SC106 (Asahi Glass); and organosiloxane polymers such as KP341 (Shin-Etsu Chemical).
[0175] Methods for manufacturing segregated layers
[0176] The present invention provides a method for manufacturing a segregation layer over a substrate, comprising: (1) applying a composition to the substrate, wherein the segregation composition comprises a solvent (A), a siloxane polymer (B), and a high-carbon material (C); and (2) heating the substrate to form a segregation layer comprising an anti-reflective coating made of the siloxane polymer (B) and a spin-coated carbon coating made of the high-carbon material (C), wherein the anti-reflective coating, the spin-coated carbon coating, and the substrate are disposed sequentially.
[0177] For clarity, the numbers in parentheses in the process description indicate the order throughout this specification, unless otherwise specified. For example, step (1) is performed before step (2).
[0178] While not wishing to be bound by theory, the inventors believe that phase separation is driven by the surface energy difference and / or solubility difference between the siloxane polymer (B) and the high-carbon material (C). One aspect of the invention is that self-segregation is caused by phase separation due to the surface energy difference and / or solubility difference (preferably surface energy difference) between the siloxane polymer (B) and the high-carbon material (C).
[0179] The segregating composition of the present invention can be applied over a substrate. The term "over a substrate" can mean that the applied composition can form a coating directly on the substrate, i.e., in direct contact with the substrate, but also includes the possibility that an intermediate layer can be inserted between the substrate and the applied composition. The term "over" includes both "direct contact" and "intercalated layer".
[0180] Prior to this, the substrate surface can be pretreated, for example, with a 1,1,1,3,3,3-hexamethyldisilazane solution. The upper surface of the substrate can be flat or uneven. The substrate used can be a metal-containing substrate or a silicon-containing substrate. The substrate can be a single-layer substrate or a multilayer substrate composed of multiple substrate layers. Any known substrate can be used as the substrate, such as a silicone-coated substrate.
[0181] In one embodiment of the invention, the segregation composition is applied using a suitable device such as a spinner or coater. When applying the composition to a substrate, it is preferable that the substrate and the composition are in direct contact. Another embodiment of the invention may involve applying the segregation composition in such a manner that another thin coating layer (e.g., a substrate modification layer) is inserted between the segregation composition and the substrate. After application of the composition, heating is performed to induce phase separation, resulting in the segregation of layers of antireflective coating and spin-coated carbon coating.
[0182] The heating (2) of the present invention is typically carried out at 20–450°C for 0.1–30 minutes. Preferably, the heating is carried out in an air atmosphere, an inert gas, or a combination thereof.
[0183] For phase separation requiring a long time, heating is preferred. In this case, several heating steps are preferred. As the first heating step, low-temperature heating is preferred. As one embodiment of the invention, the substrate is heated at a low temperature under vacuum conditions; preferably from room temperature to 80°C; more preferably 50–80°C; and even more preferably 50–75°C. The heating time of the first heating step is selected from the range of 30–240 seconds (preferably 60–180 seconds, more preferably 90–150 seconds).
[0184] In a preferred embodiment of the invention, the heating process includes multiple heating steps. For example, a second, third, and fourth heating step may be added. Examples of heating conditions for the four steps are shown below. All heating steps are not always necessary for achieving the invention and can be simplified for higher yields. In a more preferred embodiment of the invention, the heating consists of two baking steps: a first heating step and a second heating step.
[0185] The second heating step can be carried out at 50-250°C (preferably 75-200°C; more preferably 100-200°C; even more preferably 125-175°C) for 0.5-30 minutes (preferably 1-20 minutes; more preferably 5-15 minutes).
[0186] The third heating step can be carried out at 100-400°C (preferably 150-300°C; more preferably 200-300°C; even more preferably 225-275°C) for 0.1-5 minutes (preferably 0.1-3 minutes; more preferably 0.5-2 minutes).
[0187] The fourth heating step can be carried out at 150-450°C (preferably 250-400°C; more preferably 300-400°C; even more preferably 325-375°C) for 0.1-5 minutes (preferably 0.1-3 minutes; more preferably 0.5-2 minutes).
[0188] Subsequent heating steps often involve high temperatures. The spin-coated carbon coating made from the high-carbon material (C) of this invention exhibits good heat resistance. Therefore, high-temperature heating can be performed in this method.
[0189] In one embodiment of the invention, the antireflective coating is made of a siloxane polymer (B) with a thickness of 50–500 nm; preferably 50–200 nm; more preferably 100–200 nm. In one embodiment of the invention, the spin-coated carbon coating is made of a high-carbon material (C) with a thickness of 100–10,000 nm; preferably 100–1,500 nm; more preferably 100–1,000 nm; further preferably 100–500 nm; and even more preferably 100–200 nm.
[0190] This invention supports the use of siloxane polymers (B) in structures that can be used as coatings to exhibit a good antireflective index. Therefore, such coatings can be used as antireflective coatings; preferably, bottom antireflective coatings. While not wishing to be bound by theory, the inventors believe that the upper interface made from the segregating composition is rich in silicon, and therefore the main component near the upper interface is a coating made from siloxane polymers (B). Therefore, coatings made from segregating compositions can be used as bottom antireflective coatings.
[0191] In one embodiment of the invention, the coating is made of the composition of the invention, and its thickness, as the sum of the antireflective coating and the spin-coated carbon coating, is 150 to 2,000 nm (preferably 150 to 1,000 nm; more preferably 150 to 500 nm; even more preferably 150 to 200 nm).
[0192] Both antireflective coatings made from siloxane polymers (B) and spin-coated carbon coatings made from high-carbon coatings can exhibit good etch resistance. Segregated layers can also exhibit good etch resistance. The atomic content of the spin-coated carbon coating can be altered by modifying the high-carbon material (C) and other solid components, thus providing a favorable etching rate for processes using this segregated composition. Solid components, including the high-carbon material (C), can exhibit good gap-filling properties, thereby allowing this segregated composition to be applied to uneven substrates.
[0193] Formation of photoresist layer
[0194] The present invention also provides a method for manufacturing a photoresist layer, comprising (3) applying a photoresist composition over the segregation layer, and (4) heating the substrate to form a photoresist layer.
[0195] The photoresist composition is applied over the segregated layer as described above. The term "over the segregated layer" can mean that the applied photoresist composition can form a layer directly on the segregated layer, i.e., in direct contact with the upper segregated layer, but it also includes the possibility that an intermediate layer can be inserted between the upper segregated layer and the applied photoresist composition. Preferably, the applied photoresist composition forms a layer directly on the segregated layer.
[0196] Known methods can be used for this application, such as spin coating. The applied photoresist composition is heated to remove the solvent from the composition, thereby forming a photoresist layer. The heating temperature can vary depending on the composition used, but is preferably 70–150°C (more preferably 90–150°C, and even more preferably 100–140°C). The heating can be carried out on a hot plate for 10–180 seconds, preferably 30–90 seconds, or in a hot atmosphere (e.g., in a clean oven) for 1–30 minutes. The thickness of the formed photoresist layer is preferably 0.40–5.00 μm (more preferably 0.40–3.00 μm, and even more preferably 0.50–2.00 μm).
[0197] Formation of photoresist patterns
[0198] The present invention provides a method for manufacturing a photoresist pattern, comprising (5) exposing the photoresist layer and (6) developing the exposed layer to form a photoresist pattern.
[0199] The photoresist layer reacts under light / irradiation exposure. Both positive and negative photoresists can be used. In a positive photoresist layer, the irradiated portion increases the solubility of the developer. Other layers (such as TARC) can be formed on the photoresist layer.
[0200] The photoresist layer is exposed through a given mask. There are no particular limitations on the wavelength of the light used for exposure. Exposure is preferably performed using light with a wavelength of 13.5–365 nm (preferably 13.5–248 nm). KrF excimer lasers (248 nm), ArF excimer lasers (193 nm), or extreme ultraviolet light (13.5 nm) are preferred examples; KrF excimer lasers are more preferred. These wavelengths may vary within ±1%.
[0201] If necessary, heating can be performed after exposure, also known as post-exposure baking (PEB). The temperature of PEB is selected from 80 to 150°C, preferably 90 to 140°C, and the heating time of PEB is selected from 0.3 to 5 minutes, preferably 0.5 to 2 minutes.
[0202] Next, development is performed using a developer. In the positive photoresist layer, the unexposed portions are removed by development, thereby forming a resist pattern. A 2.38% by mass (accepting ±1% concentration variation) aqueous solution of TMAH is an exemplary example of a developer, but is not intended to limit the scope of the invention. Additives such as surfactants can be added to the developer. The temperature of the developer is typically selected from the range of 5 to 50°C, preferably 25 to 40°C, and the development time is typically selected from the range of 10 to 300 seconds, preferably 30 to 90 seconds. Known methods such as paddle development / swirling immersion development can be used as the development method.
[0203] After development, the resist pattern can be cleaned with water or a cleaning solution, just as water and / or a cleaning solution can be used instead of developer. The pattern can then be dried, for example, by spin drying.
[0204] Etching
[0205] This invention provides a method for manufacturing a processed substrate, comprising (7) etching the aforementioned photoresist pattern as a mask, and (8) processing the substrate. This etching can form an intercalation layer and / or a pattern of the substrate. Known etching methods, such as dry etching and wet etching (preferably dry etching), can be used. The term "intercalation layer" refers to a layer between the photoresist pattern and the substrate, including segregation layers, anti-reflective coatings, and spin-coated carbon coatings. The resulting intercalation layer pattern can be used as a next mask for further processing of the underlying layer or substrate. Another aspect of the invention provides that a photoresist pattern can be used as a mask to process the segregation layer and the substrate in a single etching operation.
[0206] Wiring can be formed in the processed substrate.
[0207] The remaining layer / pattern above the substrate can be removed by known methods, such as dry etching with O2, CF4, CHF3, Cl2 or BCl3, preferably O2 or CHF3.
[0208] As one embodiment of the present invention, it is preferred to etch the anti-reflective coating with CF4 or CHF3 (more preferably CHF3), and then the etching gas is changed to O2 to etch the spin-coated carbon coating.
[0209] Device manufacturing
[0210] Subsequently, if necessary, the substrate is further processed to form a device. This further processing can be accomplished using known methods. After device formation, if necessary, the substrate is diced into wafers, which are then connected to a lead frame and encapsulated in resin. Preferably, the device is a semiconductor device, a solar cell chip, an organic light-emitting diode (OLED), or an inorganic light-emitting diode. A preferred embodiment of the device of the present invention is a semiconductor device.
[0211] Example
[0212] The invention will be described below by way of embodiments. These embodiments are given for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise stated, the term "parts" as used in the following description refers to parts by mass.
[0213] Tokyo Electron Clean Track Act 8 was used for sample coating and baking.
[0214] The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the polymer were measured by gel permeation chromatography (GPC) calibrated with polystyrene standards, and the degree of polymerization distribution (Mw / Mn) was calculated from these measurements.
[0215] Preparation Example 1 of Invention Composition 1
[0216] Polymer C2-1 was prepared using the same method described in US 9,274,426 (Synthesis of Polymer 1). The formulation was prepared by dissolving the following three materials in a mixture of PGMEA and PGME solvents. The formulation was heated to 50°C and stirred for 4 hours.
[0217]
[0218]
[0219]
[0220] 10% D-1 was prepared by dissolving decylbenzenesulfonic acid and triethylamine in a mixture of PGMEA and PGME. No heating was performed, but the mixture was stirred for 10 minutes. This 10% D-1 was then added to the above solution, both at room temperature.
[0221]
[0222] Di(PGMEA) and n-decyl acetate were then added to the solution, along with siloxane polymer 1. The solution was then heated to 50°C and maintained for 1 hour. The solute was visually confirmed to have dissolved.
[0223] After cooling, the mixture is filtered through a 0.2 μm polypropylene filter to obtain composition 1 of the invention.
[0224]
[0225] Table 1 below describes the mass percentage of each component and solvent in the solution.
[0226] [Table 1]
[0227] Polymer C2-1 4.49% C3-1 2.16% E-1 0.66% D-1 0.27% PGMEA 56.17% PGME 23.86% n-Decyl acetate 3.98% Di(PGMEA) 7.95% Siloxane polymer 1 0.46% total 100.00%
[0228] Preparation Examples of Invention Compositions 2-7
[0229] Preparation of Example 2-7: Work Components 2-7
[0230] The preparation was carried out in the same manner as in Preparation Example 1, except that siloxane polymer 1 was replaced with siloxane polymers 2, 3, 4, 5, 6 and 7 to obtain the inventive compositions 2, 3, 4, 5, 6 and 7.
[0231]
[0232]
[0233]
[0234]
[0235]
[0236]
[0237] Synthetic chemical reaction of siloxane polymer 2
[0238]
[0239] Trimethoxy(methyl)silane (3.178 g; 23.330 mmol; 1.00 equivalent), tetraethyl orthosilicate (3.646 g; 17.500 mmol; 0.75 equivalent), 3-(trimethoxysilyl)propyl methacrylate (4.346 g; 17.500 mmol; 0.75 equivalent), and propan-2-ol (13.000 g; 216.324 mmol; 9.27 equivalent) were weighed directly (in air) into a 100 mL three-necked RBF (round-bottom flask). The mixture was stirred in an ice-water bath until the temperature reached 0°C. A 25% aqueous solution of tetramethylammonium hydroxide (4.120 g; 11.300 mmol; 0.48 equivalent) was added in portions over approximately 2 minutes. The reaction was slightly exothermic. The temperature was raised to 10°C after the addition. Once the addition was complete, the ice-water bath was removed. The solution was stirred at 25°C (external) for 2 hours. The mixture remained a clear, colorless solution. Ethoxytrimethylsilane (5.000 ml; 31.493 mmol; 1.35 equivalents) was added, and the mixture was stirred at 25°C for another 2 hours.
[0240] Add deionized water (33.6 g), hydrochloric acid (32%, 1.200 g; 11.519 mmol; 0.49 equivalents), and n-propyl acetate (16.800 g; 164.493 mmol; 7.05 equivalents) to a 100 mL Erlenmeyer flask. While stirring at 1,000 rpm, pour the reaction mixture from the RBF (a clear, colorless solution) into the Erlenmeyer flask to create a white, turbulent solution. Stir the mixture for 30 minutes. Transfer the mixture to a separatory funnel; wait 10 minutes until complete phase separation occurs. The polymer is in the upper organic phase. The upper organic layer is slightly milky white. Separate and discard the bottom aqueous phase (pH = 1). Add deionized water (33.6 g) to the organic phase and shake thoroughly. Add n-propyl acetate (6.5 g), shake the mixture, and let it stand overnight. No separation is achieved. Add 6.5 g of isopropanol. Remove and discard the bottom layer. Repeat the washing process until the pH reaches 7.
[0241] The organic phase was first rotary evaporated to 80 mbar, then 10 g of PGMEA was added. The mixture was further rotary evaporated to 23 mbar, resulting in a clear, colorless solution (13.5 g). As a precaution, the solution was filtered through a 0.45 μm syringe filter. The molecular weight was determined by GPC elution with THF (tetrahydrofuran). The solids content (150 °C, 30 min) was found to be 48.4%.
[0242] Mn Mw Mw / Mn 2426 5159 2.13
[0244] Synthetic chemical reaction of siloxane polymer 3
[0245]
[0246] Trimethoxy(methyl)silane (3.178 g; 23.330 mmol; 1.00 equivalent), tetraethyl orthosilicate (3.646 g; 17.500 mmol; 0.75 equivalent), 2-methyl-N-[3-(trimethoxysilyl)propyl]prop-2-enamide (4.329 g; 17.500 mmol; 0.75 equivalent), and propan-2-ol (13.000 g; 216.324 mmol; 9.27 equivalent) were weighed directly (in air) into a 100 mL three-necked round-bottom flask. The mixture was stirred at 600 rpm in an ice-water bath until the temperature reached 0 °C (internal temperature). A 25% aqueous solution of tetramethylammonium hydroxide (4.120 g; 11.300 mmol; 0.48 equivalent) was added in portions over approximately 2 minutes. The solution was stirred in the cooling bath for 15 minutes, and then the cooling bath was removed. The reaction was continued at room temperature for another 1 hour and 45 minutes. The mixture remained a clear, colorless solution (slightly pale yellow).
[0247] Add ethoxytrimethylsilane (5.000 mL; 31.493 mmol; 1.35 equivalents) and stir the mixture at 25 °C for 4 hours. Add deionized water (33.6 g), hydrochloric acid (32%, 1.200 g; 11.519 mmol; 0.49 equivalents), and n-propyl acetate (16.800 g; 164.493 mmol; 7.05 equivalents) to a 100 mL Erlenmeyer flask. While stirring at 1,000 rpm, pour the reaction mixture from the RBF (a clear, colorless solution) into the Erlenmeyer flask to create a white, turbulent solution. Stir the mixture for 30 minutes and then transfer it to a separatory funnel. Wait 10 minutes until complete phase separation occurs. Separate and discard the bottom aqueous phase (pH = 5). Add deionized water (33.6 g) to the organic phase and shake thoroughly. Then remove and discard the bottom layer (pH 7).
[0248] The organic phase was first rotary evaporated to 80 mbar, then 9 g of PGMEA was added. The mixture was further rotary evaporated to 23 mbar, resulting in a clear, colorless solution (14.5 g). As a precaution, the solution was filtered through a syringe 0.45 μm filter. The solids content (150 °C, 30 min) was 54%. The molecular weight was determined by GPC elution with THF.
[0249] Mn Mw Mw / Mn 1762 2633 1.49
[0251] Synthetic chemical reaction of siloxane polymer 6
[0252]
[0253] Trimethoxy(methyl)silane (2.724 g; 20.000 mmol; 1.00 equivalent), tetraethyl orthosilicate (1.042 g; 5.000 mmol; 0.25 equivalent), 3,4-dimethyl-1-(3-triethoxysilylpropyl)pyrrole-2,5-dione (8.237 g; 25.000 mmol; 1.25 equivalent), and propan-2-ol (13.000 g; 216.324 mmol; 10.82 equivalent) were weighed directly (in air) into 100 mL of three-necked RBF. The mixture was stirred at 600 rpm in an ice-water bath until the temperature reached 5 °C (internal temperature). Tetramethylammonium hydroxide (25% aqueous solution, 4.120 g; 11.300 mmol; 0.56 equivalent) was added dropwise over 3 minutes. The reaction was slightly exothermic, and the temperature increased by 5 °C to 10 °C after the addition. Once the addition is complete, remove the ice-water bath. The colorless solution is stable at 18°C and stirred for 2 hours. Add ethoxytrimethylsilane (5.000 ml; 31.493 mmol; 1.57 equivalents) in a single addition at room temperature. Stir the solution for another 2 hours.
[0254] Add deionized water (33.6 g), hydrochloric acid (32%, 1.240 g; 11.903 mmol; 0.60 equivalents), and n-propyl acetate (16.800 g; 164.493 mmol; 8.22 equivalents) to a conical flask (100 ml). While stirring at 1,000 rpm, pour the reaction mixture from the RBF (a clear, colorless solution) into the conical flask to create a white, turbulent solution. Stir the mixture for 0.5 hours, then transfer it to a separatory funnel. Wait 20 minutes for complete phase separation to occur. The polymer is in the upper organic phase. Separate and discard the bottom aqueous phase (pH = 6). Add deionized water (33.6 g) and propan-2-ol (6.5 g) to the organic phase and shake thoroughly. Phase separation occurs within 10 minutes. The bottom layer is then removed and discarded (pH 7). PGMEA (17 g) was added to the organic phase and the mixture was rotary evaporated to 4 mbar, resulting in a pale yellow viscous solution (10.6 g). The solids content (150 °C, 30 min) was 59%. The molecular weight was determined by GPC elution with THF.
[0255] Mn Mw Mw / Mn 1707 2490 1.46
[0257] Synthetic chemical reaction of siloxane polymer 7
[0258]
[0259] Weigh directly (in air) diethoxydimethylsilane (2.966 g; 20.000 mmol; 2.00 equivalent), diethoxymethylvinylsilane (3.206 g; 20.000 mmol; 2.00 equivalent), and dimethoxy[4-(methoxymethoxy)phenyl]methylsilane (2.423 g; 10.000 mmol; 1.00 equivalent) into a 25 ml round-bottom flask. Add all at once. The mixture was prepared in 900 hydroxide form (2.500 g; 27.427 mmol; 2.74 equivalents) and stirred at 30 °C for 18 h, then at 50 °C for 48 h. The temperature was raised to 80 °C and stirred for 30 h, then cooled to room temperature, and ether (10 ml) was added. The mixture was filtered through a 0.45 μm syringe filter. The filtrate was rotary evaporated to dryness to maximum vacuum (10 mbar, 50 °C) to give a thick, pale yellow oil (3.86 g). The molecular weight was determined by GPC elution with THF.
[0260] Mn Mw Mw / Mn 6764 17118 2.53
[0262] Substrate preparation
[0263] Each composition was spin-coated onto a CZ-Si wafer. The spin conditions were 500 rpm for 10 seconds, followed by 1,500 rpm for 60 seconds, with an acceleration of 500 rpm.
[0264] The wafer is then heated on a hot plate at 70°C for 2 minutes. It is then transferred to another hot plate and heated at 150°C for 10 minutes, then at 250°C for 1 minute, and finally at 350°C for 2 minutes.
[0265] Uniformity assessment
[0266] The macroscopic film uniformity of each silicon wafer is excellent. No visible defects or color variations are observed with the naked eye. Cross-sectional SEM reveals no material degassing, voids, or defects. Atomic force microscopy (AFM) imaging at 20 μm... 2 The region exhibits good nanomorphology and uniform phase. Surface roughness is <2–4 nm.
[0267] Contact angle assessment
[0268] The compositions listed in the table below were used to evaluate contact angles. The comparative composition SOC was prepared in the same manner as in Preparation Example 1, except that a siloxane polymer was not used. The substrate was prepared in the same manner as described above.
[0269] The contact angle of pure water droplets on a coated wafer surface was measured using a camera. Measurements were repeated at six different locations across the entire surface. The results indicate that phase separation is driven to bring the siloxane-rich interface to the upper surface.
[0270] [Table 2]
[0271] Invention Composition 1 85±1 Inventive Composition 2 82±2 Inventive Composition 3 90±2 Inventive Composition 4 93±2 Inventive Composition 5 85±1 Inventive Composition 6 92±1 Comparative composition SOC 69±5
[0272] Silicon content assessment
[0273] Silicon content was assessed using X-ray photoelectron spectroscopy (XPS) on each substrate. The content was first checked on the surface (0 nm). Then, CHF3 etching was performed to further assess the silicon content. The results obtained are as follows: Figure 1 As shown in the figure. The results show a silicon-rich interface, with silicon content decreasing with film depth.
[0274] Preparation Example 8 of Invention Composition 8
[0275] Siloxane polymer 7 and D-1 (100:20.63 by mass) were dissolved in PGMEA to prepare a 15% by mass solution. The solution was then heated to 50°C and held for 1 hour. The dissolution of the solute was visually confirmed. After cooling, the mixture was filtered through a 0.2 μm polypropylene filter to obtain composition 8 of the invention.
[0276] Solvent resistance assessment
[0277] The inventive composition 8 was spin-coated onto a glass substrate at 500 rpm for 10 seconds, then at 1,000 rpm for 30 seconds. The substrate was then dried on a hot plate at 100°C for 2 minutes. The substrate was then heated on a hot plate at 350°C for 5 minutes. The thickness of the resulting coating was measured using a profilometer. The substrate was then covered with PGMEA for 2 minutes. Its volume allowed the surface tension of the PGMEA to retain the solvent on the substrate and prevent it from spreading to the edges. The substrate was then rotated at 1,500 rpm for 10 seconds and heated to 100°C for 2 minutes to remove any residual solvent. The thickness was measured again using a profilometer. The film retention rate was 98%.
[0278] Thermogravimetric analysis
[0279] The substrate was weighed. The inventive composition 8 was spin-coated onto a glass substrate at 500 rpm for 10 seconds, then rotated at 1,000 rpm for 30 seconds and baked at 70°C for 2 minutes to dry the film. The substrate with the coating was then weighed. The substrate was heated from 30°C to 150°C at a rate increasing by 40°C per minute. It was then held at 150°C for 10 minutes. It was then heated from 150°C to 250°C at a rate increasing by 40°C per minute and held at 250°C for 2 minutes. It was then heated from 250°C to 350°C at a rate increasing by 40°C per minute and held at 350°C for 2 minutes. The percentage of mass loss was negatively correlated with the Mw of the siloxane. The film retention rate after these conditions was 96% by mass.
Claims
1. A method for fabricating a segregation layer over a substrate, comprising: (1) Applying a composition over the substrate, wherein the composition comprises a solvent (A), a siloxane polymer (B), and a high-carbon material (C); and (2) The substrate is heated to form a segregation layer of an anti-reflective coating made of a siloxane polymer (B) and a spin-coated carbon coating made of a high-carbon material (C), wherein the anti-reflective coating, the spin-coated carbon coating and the substrate are arranged sequentially. The thickness of the anti-reflective coating is 50~500nm; The thickness of the spin-coated carbon coating is 100~10,000 nm. The composition segregates into the anti-reflective coating and the spin-coated carbon coating. This self-segregation is caused by the difference in surface energy and / or solubility between the siloxane polymer (B) and the high-carbon material (C) through phase separation. The siloxane polymer (B) comprises at least one unit selected from the group consisting of unit B1, unit B2 and unit B3; Units B1, B2, and B3 are each represented by equations B1, B2, and B3 respectively: Formula B1 Ah 11 It is C 1-5 Aliphatic hydrocarbons, R 12 Yes - Ah 12 -O-Ah 12 -O-*, -Si(H) p12 (Ah 12 ) q12 -O-Si(H) p12 (Ah 12 ) q12 Or a single key that connects to other units. Ah 12 It is C 1-5 Aliphatic hydrocarbons, p12 = 0, 1, 2, or 3, q12 = 0, 1, 2, or 3, p12 + q12 = 3. L 11 It is a single bond or -O-, while n 11 It is the number of repetitions of unit B1; Formula B2 R 21 Yes - Ah 21 -O-Ah 21 -O-*, -Si(H) p21 (Ah 21 ) q21 -O-Si(H) p21 (Ah 21 ) q21 Or a single key that connects to other units. R 22 Yes - Ah 22 -O-Ah 22 -O-*, -Si(H) p22 (Ah 22 ) q22 -O-Si(H) p22 (Ah 22 ) q22 Or a single key that connects to other units. Ah 21 and Ah 22 Each is C independently 1-5 Aliphatic hydrocarbons, p21, p22, q21, and q22 are each independently 0, 1, 2, or 3. p21 + q21 = p22 + q22 = 3, L 21 It is a single bond or -O-, while n 21 It is the number of repetitions of unit B2; Formula B3 R 31 Yes - Ah 31 -O-Ah 31 -O-*, -Si(H) p31 (Ah 31 ) q31 -O-Si(H) p31 (Ah 31 ) q31 Or a single key that connects to other units. Ah 31 It is C 1-5 Aliphatic hydrocarbons, p31 = 0, 1, 2, or 3, q31 = 0, 1, 2, or 3, p31 + q31 = 3. R 32 It is a group consisting of at least two groups and / or linkers selected from the group consisting of: phenyl, phenylene, -O-, -(C=O)-, -COO-, -COOH, -NH-, C 1-5 Aliphatic hydrocarbon groups and C 1-5 Aliphatic hydrocarbon linker, L 31 It is a single bond or -O-, while n 31 The number of repetitions for unit B3; 0%≤n 11 / (n 11 +n 21 +n 31 )≤80%, 0%≤n 21 / (n 11 +n 21 +n 31 )≤80%, and 0%≤n 31 / (n 11 +n 21 +n 31 )≤80%, The high-carbon material (C) comprises at least one selected from the group consisting of unit C2 and molecule C3, each represented by the free formula C2 and C3; Formula C2 Formula C3.
2. The method according to claim 1, wherein the number of atoms contained in the spin-coated carbon coating satisfies the following formula C1; 1.5 ≤ {total number of atoms / (number of C atoms - number of O atoms)} ≤ 3.5 (Equation C1) in, The number of C atoms is the number of carbon atoms in the total number of atoms, while the number of O atoms is the number of oxygen atoms in the total number of atoms.
3. The method according to claim 1 or 2, wherein the composition further comprises a thermal acid generating agent (D) and / or a crosslinking agent (E).
4. The method according to claim 1 or 2, wherein the solvent (A) comprises an organic solvent.
5. The method according to claim 1 or 2, wherein the solvent (A) is in a mass ratio of 60 to 99% based on the total mass of the composition.
6. The method according to claim 1 or 2, wherein the heating (2) is performed at 20 to 450°C for 0.1 to 30 minutes.
7. The method according to claim 1 or 2, wherein the composition is substantially composed of a segregating composition.
8. A method for manufacturing a photoresist layer, comprising: (3) Applying a photoresist composition over the segregated layer produced by any one of claims 1 to 7; as well as (4) Heating the substrate to form a photoresist layer.
9. A method for manufacturing photoresist patterns, comprising: (5) Expose the photoresist layer manufactured by the method of claim 8; as well as (6) The exposed layer is developed to form a photoresist pattern.
10. A method for manufacturing a processed substrate, comprising: (7) The resist pattern manufactured by the method of claim 9 is used as a mask for etching; as well as (8) Process the substrate.
11. A method of manufacturing a device, comprising a substrate manufactured by the method of claim 10.
12. The method of manufacturing a device according to claim 11, further comprising forming wiring in the processed substrate.
13. A composition for self-segregating into an anti-reflective coating and spin-coating a carbon coating, comprising a solvent (A), a siloxane polymer (B), and a high-carbon material (C), The composition segregates into the anti-reflective coating and the spin-coated carbon coating. This self-segregation is caused by the difference in surface energy and / or solubility between the siloxane polymer (B) and the high-carbon material (C) through phase separation. The siloxane polymer (B) comprises at least one unit selected from the group consisting of unit B1, unit B2 and unit B3; Units B1, B2, and B3 are each represented by equations B1, B2, and B3 respectively: Formula B1 Ah 11 It is C 1-5 Aliphatic hydrocarbons, R 12 Yes - Ah 12 -O-Ah 12 -O-*, -Si(H) p12 (Ah 12 ) q12 -O-Si(H) p12 (Ah 12 ) q12 Or a single key that connects to other units. Ah 12 It is C 1-5 Aliphatic hydrocarbons, p12 = 0, 1, 2, or 3, q12 = 0, 1, 2, or 3, p12 + q12 = 3. L 11 It is a single bond or -O-, while n 11 It is the number of repetitions of unit B1; Formula B2 R 21 Yes - Ah 21 -O-Ah 21 -O-*, -Si(H) p21 (Ah 21 ) q21 -O-Si(H) p21 (Ah 21 ) q21 Or a single key that connects to other units. R 22 Yes - Ah 22 -O-Ah 22 -O-*, -Si(H) p22 (Ah 22 ) q22 -O-Si(H) p22 (Ah 22 ) q22 Or a single key that connects to other units. Ah 21 and Ah 22 Each is C independently 1-5 Aliphatic hydrocarbons, p21, p22, q21, and q22 are each independently 0, 1, 2, or 3. p21 + q21 = p22 + q22 = 3, L 21 It is a single bond or -O-, while n 21 It is the number of repetitions of unit B2; Formula B3 R 31 Yes - Ah 31 -O-Ah 31 -O-*, -Si(H) p31 (Ah 31 ) q31 -O-Si(H) p31 (Ah 31 ) q31 Or a single key that connects to other units. Ah 31 It is C 1-5 Aliphatic hydrocarbons, p31 = 0, 1, 2, or 3, q31 = 0, 1, 2, or 3, p31 + q31 = 3. R 32 It is a group consisting of at least two groups and / or linkers selected from the group consisting of: phenyl, phenylene, -O-, -(C=O)-, -COO-, -COOH, -NH-, C 1-5 Aliphatic hydrocarbon groups and C 1-5 Aliphatic hydrocarbon linker, L 31 It is a single bond or -O-, while n 31 The number of repetitions for unit B3; 0%≤n 11 / (n 11 +n 21 +n 31 )≤80%, 0%≤n 21 / (n 11 +n 21 +n 31 )≤80%, and 0%≤n 31 / (n 11 +n 21 +n 31 )≤80%, The high-carbon material (C) comprises at least one selected from the group consisting of unit C2 and molecule C3, each represented by the free formula C2 and C3; Formula C2 Formula C3.
Citation Information
Patent Citations
Method to Form a CMOS Image Sensor
US20140061738A1
Antireflective coating compositions and processes thereof
US9274426B2
Negative-type photosensitive resin composition, partition wall for use in optical elements and manufacturing method thereof, manufacturing method of an optical element having said partition walls, and ink-epellent agent solution
CN103238111A